Strategies of distance self-study at the Zaporizhzhia state medical university, department of histology, cytology and embryology - Makyeyeva, L. V.; Alieva, O. G.; Potots’ka, O. I.; Popazova, O. O.; Zidrashko, G. A.; Макеева, Л. В.; Алиева, Е. Г.; Потоцкая, Е. И.; Попазова, Е. А.; Зидрашко, Г. А.; Макєєва, Людмила Валеріївна; Алієва, Олена Геннадіївна; et al. (My University, 2021)
Remote self-training of students is not only designed to reduce classroom hours, but is also necessary during the COVID-19 pandemic. In 2016, our department’s teachers introduced online courses for self-training and testing students ‘ knowledge on the edX platform. As a result, the absolute and qualitative academic performance of students has increased.Дистанционная самоподготовка студентов призвана не только сократить аудиторные часы, но и является необходимой во время пандемии COVID-19. Преподавателями нашей кафедры еще в 2016 году внедрены онлайн курсы для самоподготовки и проверки знаний студентов на платформе edX. Как результат, повысилась абсолютная и качественная успеваемость студентов.
Стратегии дистанционной самоподготовки в Запорожском государственном медицинском университете, на кафедре гистологии, цитологи и эмбриологии
Keywords: distance learning; self-training; COVID-19 pandemic; online courses; academic performance; дистанционное обучение; самоподготовка; пандемия COVID-19; онлайн-курсы; успеваемость